2022
DOI: 10.18805/ijar.b-4876
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Occurrence and Classification of Long Bone Fractures in Dogs: A Retrospective Study

Abstract: Background: Long bone fracture in small animals has become a problem of concern in urban areas as well as rural areas because of road accidents. Canine long bone fracture cases presented at surgery wards of the hospital during 2017-20 were analysed for determining their incidence, occurrence and classification of fractures. Methods: The present study was conducted on long bone fractures in dogs presented to the surgery ward of SVVU Super Speciality Veterinary Hospital, Visakhapatnam from 2017 to 2020. Detailed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Bone fractures are a prevalent health issue seen in canines and result from a multitude of contributing factors. Dogs frequently experience car accidents, falls [5], and diverse injuries inside the home, especially during training sessions [6] or as a result of being assaulted by another dog [7,8]. Nevertheless, it is essential to consider not just the fracture as a consequence but also the potential etiology of the fracture; we should ask ourselves how we could have potentially prevented the animal from having experienced a fracture [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone fractures are a prevalent health issue seen in canines and result from a multitude of contributing factors. Dogs frequently experience car accidents, falls [5], and diverse injuries inside the home, especially during training sessions [6] or as a result of being assaulted by another dog [7,8]. Nevertheless, it is essential to consider not just the fracture as a consequence but also the potential etiology of the fracture; we should ask ourselves how we could have potentially prevented the animal from having experienced a fracture [9].…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of canine breeds exist, with each breed possessing distinct genetic and physical characteristics that may contribute to the occurrence of bone fractures. Mongrel dogs have been reported to have a notable prevalence of long-bone fractures, specifically in the tibia and fibula, mostly arising from incidents involving falls from elevated positions [8]. After a scientific literature review, it was indicated that there are significant disparities between large and small canine breeds.…”
Section: Introductionmentioning
confidence: 99%